2020
DOI: 10.1108/ijse-08-2019-0476
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of corruption and firm performance: an empirical analysis from BEEPS survey

Abstract: PurposeThe link between corruption and firm performance has received considerable critical attention. However, until now, far too little attention has been paid to different dimensions of corruption and their relationship with firm performance. The aim of this paper is, therefore, to examine the relationship between dimensions of corruption and firm productivity.Design/methodology/approachThis paper uses the fifth wave of Business Environment and Enterprise Performance Survey, which is based on the survey ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Aralica et al, (2018) and Ojeka et al (2019) support the findings that control of corruption improves the firm’s performance in Central and Southeastern Europe and Nigeria, respectively. In contrast, Ashyrov and Akuffo (2020) find that corruption and bribery promote the firm’s productivity.…”
Section: Literature Reviewmentioning
confidence: 75%
“…Aralica et al, (2018) and Ojeka et al (2019) support the findings that control of corruption improves the firm’s performance in Central and Southeastern Europe and Nigeria, respectively. In contrast, Ashyrov and Akuffo (2020) find that corruption and bribery promote the firm’s productivity.…”
Section: Literature Reviewmentioning
confidence: 75%
“…However, Seck (2020) has recently argued that bribery could grease the wheels of commerce for small and expanding firms by increasing their labor productivity, investment and likelihood to enter export markets; meanwhile, corruption could also sand the wheels for mature firms and harm their performance. In another study, Ashyrov and Akuffo (2020) have shown that political corruption was positively associated with firms’ labor productivity in post-communist economies; in other words, firms could exploit their political connections with the government to enhance their operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…conducted through misuse of authority or power by public (government) or private (firms) officeholders for private gain and benefit, financial or otherwise.” There are several reasons to explain why firms engage in corruption. Although this illegal activity allows firms to surpass bureaucratic processes, complex regulations (Lui, 1985) and develop networks or social capital to exceed the challenges of entering a new market (Jong et al, 2012), which promotes growth and achieves higher financial performance (Ashyrov & Akuffo, 2020; Williams & Kedir, 2016), firms may face reduced financial performance because of excessive bribe payment. Moreover, from previous empirical evidence, family firms perform a deeper concern for their image with the public and are not willing to engage in unethical activities (López-Pérez et al, 2018).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%